Economic Failures of Nehru and Indira Gandhi - "Gujral, M L" (Sahibabad, 1979)
This book deals primarily with the economic failures of Nehru and Indira Gandhi. Work on it was begun in early 1975, when the country was on the brink of a cataclysm. In July 1975, it had to be abandoned as it was clear that for the time being at least, its publication was completely out of question. With the rout of the Congress party at the hustings in March 1977, the task was resumed. In March 1978, Mr Jayaprakash Narayan penned a foreword for the book. He was satisfied with the restoration of civil liberties by the Janata party but extremely unhappy with its infighting and non-performance. In March 1979 an epilogue on the utter failure of the Janata government became necessary and its leaders were warned of the doom ahead. It has overtaken them and the Morarji government, as predicted has fallen.
Keywords: Economic history